Microbe-mediated host defence drives the evolution of reduced pathogen virulence - Suzanne A. Ford (Nature Portfolio, 2016)
Some microbes protect their hosts from pathogens and likely drive pathogens’ evolution. Here, Fordet al. show that a host-protective microbe selects for reduced virulence of a pathogen in the model organism Caenorhabditis elegans.